Chandragupta II, coin-img1 - Wiki commons (2022)
An 8-gram gold coin featuring Chandragupta II astride a caparisoned horse with a bow in his left hand. The name Chandragupta appears in the upper left quadrant. Attribution: I, PHGCOM, CC BY-SA 3.0 <http://creativecommons.org/licenses/by-sa/3.0/>, via Wikimedia Commons